Relationship between social support, dysfunctional attitude, and perceived academic stress in students of Ferdows school of medical sciences - Raheleh Rajabi; Hassan Eslami Aliabadi; Seyyedeh Sara Afrazandeh (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Students constantly go through experiences that can be a source of physical, emotional, or psychological stress. Dysfunctional attitudes are the root of numerous mental health problems. On the other hand, perceived social support is recognized as one of the most effective solutions in the treatment of stress and its related disorders. The present study aimed to assess the relationship of social support and dysfunctional attitude with perceived academic stress in the students of Ferdows School of Medical Sciences. Materials & Methods: This descriptive-correlational study was conducted on 121 students of Ferdows School of Allied Medicine and Public Health who were selected via stratified sampling method in the academic year 2019-2020. The data collection tools were demographic characteristics form and three standard questionnaires of social support appraisals (SS-A) scale, Vaux A, Student Life Stress Inventory (SLSI), and Dysfunctional Attitude Scale(DAS-26). Data were analyzed in SPSS software (version 22) using descriptive (mean and standard deviation) and inferential statistics (Kolmogorov-Smirnov test to determine whether sample data is normally distributed, Pearson and Spearman correlation test to check the relationship between variables, and independent t-test and analysis of variance to compare means between two groups. A p-value of 0.05 was considered statistically significant. Results: The mean scores of academic stress and perceived social support of students were reported as 2.61±0.49 and 2.42±0.47, respectively, which were lower than the average. Moreover, the mean score of dysfunctional attitude (110.24±78.5) was higher than the standard. Pearson's correlation test pointed to a significant relationship between social support and academic stress (r=0.36; P< 0.001), dysfunctional attitude and academic stress (P=0.006; r = -0.24) and dysfunctional attitude and social support (P=0.005; R=-0.25). Conclusion: The results of the present study pointed out that the variables were closely related to each other, highlighting the importance of these issues in student life. In other words, in order to adjust to academic stress, which is the cause of failure and disruption in academic performance, attention should be paid to various factors at the level of the university, society, and most importantly, family where a person is raised. In this regard, culture building is necessary at the university, society, and family level to shape people's attitudes positively and develop creative thinking based on hope and a burning desire for construction.